Stressors Experienced During Clinical Placement Among Diploma Nursing Students In Kolej Poly-tech Mara, Kota Bharu, Kelantan - Zulainah Osman; Chan , Siok Gim (Lincoln University College, Asia Pacific Higher Learning Sdn Bhd, 2018)
The aim of this project was to determine stress levels and to identify the main stressors that contribute to stress among Kolej Poly-Tech Mara (KPTM) nursing students during their clinical placement in order to help them overcome it. A total of 324 respondents undergoing training at KPTM participated in this project. The questionnaire consisting of six common stressors with 30 items using a 5-point Likert Scale was used to measure the level of stress among the respondents during their clinical placement. The data collected was examined for normal distribution, and inferential statistics such as correlations were used to seek relationships. The results indicated that the main stressors that contributed to stress among KPTM nursing students were from both environment, along with assignments and workload. There was moderate level of stress among KPTM nursing students during clinical placement and the factor that contributed to stress was due to the the possibility of making an error. Clinical placement is an essential component for nursing student's training. The practice allows nursing students the opportunity to relate the theory into practice during nursing care towards the patients. Findingsfrom this study will provide the nursing educators, clinical instructors with a meaningful understanding of the importance of clinical placement experience.